IMPLICATIONS OF LAND RECLAMATION ON LIVELIHOOD, EMPLOYMENT, EDUCATION AND INFRASTRUCTURE IN SELECTED RIVERINE AREAS OF RIVERS STATE, SOUTHERN NIGERIA - Michael .U. Didia; A. E. Gobo; Joshua Brown (American Journals Publishing, 2022)
The study evaluated the impact of land reclamation activities in the study locations. Land Reclamation is the process of gaining more land from the sea or coastal wetland or the expansion of land capacity for industrial and infrastructural development. Quantitative and qualitative research method was adopted for the purpose of this study. Field observations, questionnaire survey and landsat imagery of land cover changes of the year 1986 and 2018 were retrieved from the study area. The research revealed the spatial pattern of land reclamation; it also revealed the socioeconomic implications of land reclamation activities across the study area and its role in the delivery of developmental projects.
Keywords: Land Reclamation; Rivers State Reclamation; Reclamation impact